ISLAMIC ECONOMIC CONCEPTS IN THE UMAYYAH, ABASSIYYAH, AND OTTOMAN EMPIRE BASED ON HISTORICAL APPROACHES - Muhammad, Nurdin I; Yetty, Yetty; Suar, Abi (Asian Journal of Islamic Economic Studies, 2024)
The concept of Islamic economics has emerged since Islam was revealed through the Prophet Muhammad SAW which was then continued during the leadership of the khulafaur Rashidun. It was then that Islam began to influence the world. Islam experienced progress and setbacks, this also happened to the economy of its time, the progress of Islamic power achieved during the Abbasid period, and its collapse when it was attacked by the Mongols. This study uses historical methods using a descriptive qualitative approach. The purpose of this study is to determine the economic concept of the Umayyad, Abassiyyah, and Ottoman Turks based on a historical approach. The output of this research is that the Umayyads became the first government in Islam to implement a monarchiheridetic system or what is commonly called hereditary power. During his reign he was able to build a well-organized Muslim society as a conducive condition for his economy. The Abbasid dynasty, which was established from 750 AD - 1258 AD, at this time was called "The Golden Age" which means it reached the peak of glory, both in the fields of economy, civilization and power. During Al-Mahdi's reign, the country's economy began to increase by increasing the agricultural sector through irrigation and increasing mining output. Sulaiman Al Qanuni's leadership was the golden peak of Islam in the Ottoman Empire, he succeeded in carrying out laws based on Islamic law. In the economic field, at the peak of its progress, all important areas and cities that were centers of trade and economy fell into his hands.